Dataset on the relationship between students’ attitude towards, and performance in mathematics word problems, mediated by active learning heuristic problem-solving approach - Wakhata, Robert; Mutarutinya, Védaste; Balimuttajjo, Sudi (Data in Brief, 2023)
The present data was applied to investigate the relation- ship between students’ attitude towards, and performance in mathematics word problems (MWTs), mediated by the active learning heuristic problem-solving (ALHPS) approach. Specif- ically, the data reports on the correlation between students’ performance and their attitude towards linear programming (LP) word tasks (ATLPWTs). Four types of data were col- lected from 608 grade 11 students who were selected from eight secondary schools (both public and private). The partic- ipants were from two districts: Mukono and Mbale in Central Uganda and Eastern Uganda respectively. A mixed methods approach with a quasi-experimental non-equivalent group design was adopted. The data collection tools included stan- dardized LP achievement tests (LPATs) for pre-test and post- test, the attitude towards mathematics inventory–short form (ATMI-SF), a standardized active learning heuristic problem- solving tool, and an observation scale. The data were col- lected from October 2020 to February 2021. All the four tools were validated by mathematics experts, pilot-tested and found reliable and suitable for measuring students’ per- formance and attitude towards LP word tasks. To achieve the purpose of the study, eight intact classes from the sampled schools were selected using the cluster random sampling method. Of these, and by a toss of a coin, four were randomly assigned to the comparison group while the other four were randomly assigned to the treatment group. All teachers from the treatment group were trained on the application of the ALHPS approach before intervention. The participants’ de- mographic data (identification numbers, age, gender, school status, and school location) were presented together with the pre-test and the post-test raw scores obtained before and after intervention respectively. The LPMWPs test items were administered to the students to explore and assess their problem-solving (PS), graphing (G), and Newman error analy- sis strategies. Students’ percentage scores in the pre-test and post-test were based on mathematizing word problems to optimization of LP problems. Data were analyzed in line with the purpose of the study, and the stated objectives. This data supplements other data sets and empirical findings on the mathematization of mathematics word problems, problem- solving strategies, graphing and error analysis prompts. This data may serve and provide some insights into the extent to which ALHPS strategies support students’ conceptual under- standing, procedural fluency, and reasoning among learners in secondary schools and beyond. The LPMWPs test items in the supplementary data files can also act as a basis for the application of mathematics in real-life scenarios beyond the compulsory level. The data is intended to develop, support, and strengthen students’ problem-solving and critical think- ing skills with the main goal of enhancing instruction and assessment in secondary schools and beyond.
Keywords: Active learning; Attitude; Heuristic problem-solving; Mathematics; Secondary schools; Linear programming